Comparing the effectiveness of behavioral activation group therapy and treatment based on acceptance and commitment on depression and quality of life of people with cancer - Darbandi, Mohsen; Amini, Naser; Deyreh, Ezat; Mirzaei, Kamran; Azadi, Shahdokht (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and purpose: Cancer is a potential fatal disease that is mainly caused by environmental factors and cellular mutations. The purpose of the present study is to treat behavioral activation and acceptance and commitment -based treatment (ACT) to reduce the severity of the symptoms of depression and improve the quality of life in patients with cancer. Method: The present study is applied in terms of the purpose and in terms of the method of a semi-experimental section with pre-test-post-test design. The statistical population includes all people with cancer referred to the oncology departments of hospitals and clinics in Bushehr during the research. Of these, 30 are selected by available sampling methods and are randomly replaced in three groups (two experimental groups and one certificate). Each group consists of 10 people. After obtaining participants' satisfaction and adhering to ethics, Quality Questionnaires (Jenicson et al., 1) and depression (Beck, Stire and Garbin, 1) were executed as a pre -test on all participants. The first experimental group was trained in the behavioral activation protocol based on the Golan et al. (2003), the second group was under admission and commitment training based on the Hayez et al. All sessions of the experimental group were held through Skype due to the Cronist's conditions. Results: The mean difference of depression scores and quality of life was significant between both experimental groups with a testimony group (P